THE POLITICS OF GLOBAL RESPONSE TO COVID-19: Implications for the International Communication of Health Care Systems - Eranfeno, Gizachew Nemomsa (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2020)
This article analyzes global responses to the outbreak and spread of Covid-19. Specifically, how international communications on the management of Covid-19 by nations and institutions face challenges due to lack of preparedness and capacity of the countries to tackle the virus's spread. Also, how diplomatic relations for cooperation change into conflicts among economic and political rivals in the world. By reviewing selected online news media coverage and social networking sites of public figures and leaders to respond to the epidemics from January-April 2020, this article also draws upon Wallerstein’s world-systems theory as a conceptual framework. The findings indicate that Covid-19 spread at an alarming rate worldwide and contribute to the politicization of global response to and cooperation on Covid-19. The study concludes that Wallerstein’s categorization of the world through the lens of world-systems theory will no more explain the global health care system's nature.  Hence, the author suggests a call for Jan N. Pieterse’s critical globalism to improve the health care system's global discourse. Global integration through media discourse would shape communication flows and approaches of cooperation.  It also suggested that the world from the core, periphery, and semi-periphery should discuss to tackle the spread of the virus at this time and global environmental crisis in the future. To cite this article (7th APA style):Eranfeno, G. N. (2020). The Politics of Global Response to Covid-19: Implications for the International Communication of Health Care Systems. Journal Communication Spectrum: Capturing New Perspectives in Communication, 10(2), xx-xx. http://dx.doi.org/10.36782/jcs.v10i2.2024